The trusted committer in InnerSource keeping the software and the community healthy - Gruetter, Georg (O'Reilly Media, 2019)
"The Trusted Committer (TC) role is a key role in every InnerSource community. Think of the TC as the person in your community you trust with important technical decisions who will mentor Trusted Contributors and help them push their contributions over the finish line. It is both a demanding and a rewarding role to fulfill. It goes far beyond being an opinionated gatekeeper and is vital to the success of any InnerSource effort. This video details the responsibilities and requirements of being a TC. For best results, learners should first watch the O'Reilly video "Introduction to InnerSource" and have a general understanding of the InnerSource TC and Contributor roles."--Resource description page
Title from title screen (viewed April 11, 2019)
Keywords: Open source software; Teams in the workplace; Information technology -- Management; Project management; Leadership; Logiciels libres; Équipes de travail; Technologie de l'information; Gestion; Gestion de projet; Information technology; Management